First Physico-Chemical and Traditional Characterisation of Lake Tseny, Northwest Madagascar - Randrianandrianina, Felicien Herbert; Andriafidison, Daudet; Razafimanahaka, Hanta Julie; Rasoloariniaina, Jean Robertin; Rejo-Fienena, Felicitee (European Scientific Journal, ESJ, 2023)
This study was designed to assess the biophysical structure, traditional practices and water quality of Lake Tseny in northwest Madagascar. The lake was divided into five zones: the central zone and the littoral zones (east, north, west and south). Transects and direct observation were used to estimate submerged tree and vegetation cover. Information on local traditions was collected through interviews with key people and visits to sacred sites. Water quality was assessed during the rainy and dry seasons, 2017–2018. Samples were taken twice a day, in the early morning and evening, at randomly selected points at intervals of 400m. The aquatic vegetation covered over 75% of the lakeshore. Most of the submerged tree trunks were recorded along the western area. Five sacred sites associated with eight forms of traditional taboos to reduce the potential source of water pollution were recorded in and around the lake. The lake is bowl shaped. The water was warm (T° 25.3 - 35.6 °C), slightly alkaline (pH 7.1 - 8.5), well oxygenated (DO 4.63 - 9.6 mg/l ) and less mineralised (EC 71.70 - 122.40 µS/cm). We found a seasonal difference in water quality between the rainy and dry seasons. Results showed spatial variation in water quality between zones. A comparison of the mean values with water quality standards showed that Lake Tseny has good water conditions for domestic purposes and suitable habitats for aquatic fauna throughout the year. These preliminary results provide reference data on the lake’s characteristics. Due to the increasing human activities in the area, regular monitoring of water quality and physical characteristics should be carried out.